Systematic Literature Review: Pengaruh puasa terhadap nafsu makan pada obesitas dan bukan obesitas - Raden Ayu Tanzila; irfannuddin irfannuddin; Yudianita Kesuma; Iche Andriyani Liberty (Faculty of Medicine, Universitas Andalas, 2023)
Background: Fasting is the voluntary act of abstaining from food, drink, or both, as well as from anything that breaks the fast for a certain time. In medicine, fasting has an important role in various diseases and health. Several studies have assessed the benefits of fasting in various physiological and pathological conditions, one of which is an appetite in obese and non-obese people. Objective: Writing an article in the form of a systematic literature review aims to analyze the effect of various fasting methods on appetite. Method: Systematic literature review method by taking 19 international journals, according to the specified keyword criteria. Results: From the results of the systematic review analysis, it was found that fasting affects subjective appetite by changing appetite scores and objective appetite by changing appetite regulation parameters such as leptin, ghrelin, PYY, adiponectin, and neuropeptide Y (NPY). Conclusion: It was concluded that fasting had positive benefits on appetite in both obese and healthy individuals. This systematic literature review is expected to be a reference for future researchers and further research can be carried out using a more varied literature search database.